GENESIS, GEOGRAPHY OF NANOSCOPIC MATTER AND ITS IMPORTANCE FOR FERTILITY AND ECOLOGICAL FUNCTIONING OF SOILS - B. Gradusov (Бюллетень Почвенного института им. В.В. Докучаева, 2010)
The questions of using the concepts and methods of nanoscopic research in soil science are considered. These include the concept of nanoscopic particles, fundamental features of nanoscopic substances, genesis and geography of a large number of minerals with pronounced nanoscopic properties in soils. A number of regularities of nanoscopic minerals placement in soils of Russia and neighboring countries have been revealed. The differences between the main soil types from a nanoscopic point of view. The problem of introduction of nanoscopic research methods in soil science is discussed, and the prospects of using nanosized minerals and formations in improvement of land productivity, including fertilizer production and reclamation, as well as assessment of environmental situations, and design of soil protection measures.